Indentation measurement of thin plates using 3D digital image correlation and experimental validation - Juan-Antonio Almazán-Lázaro; Elías López-Alba; Francisco-Alberto Díaz-Garrido (Results in Engineering)
Full field and non-contact methods are becoming increasingly useful to get accurate measurements of displacements in many recent research fields and industries. 3D Digital Image Correlation (3D-DIC) is one of these powerful tools, which is capable of performing out-of-plane measurements.The purpose of this work is to investigate a novel method for measuring the indentation response of materials, indirectly by applying 3D-DIC to the opposite contacted side of the area of interest. Due to the setup limitations of conventional techniques for visually measuring indentations, the method presented here enables the measurement of displacement by processing the data from the opposite surface. The response is measured across a range of thicknesses of squared clamped aluminium plates with a centred point load applied using a hemispherical indenter. The results have been compared with available analytical models as well as numerical simulations. The load, deflection and indentation have been determined throughout the process. The results have demonstrated the accuracy and feasibility of the method across various thicknesses, with potential applications in different geometries and processes.